Inhibitory effect of hydrogen sulfide on ozone-induced airway inflammation, oxidative stress, and bronchial hyperresponsiveness - P. Zhang; Li, F.; Wiegman, C. H.; Zhang, M.; Hong, Y.; Gong, J.; Chang, Y.; J.J. Zhang; Adcock, I.; Chung, K. F.; X. Zhou (American Journal of Respiratory Cell and Molecular Biology, 2015)
Exposure to ozone has been associated with airway inflammation, oxidative stress, and bronchial hyperresponsiveness. The goal of this study was to examine whether these adverse effects of ozone could be prevented or reversed by hydrogen sulfide (H2S) as a reducing agent. The H2S donor sodium (NaHS) (2 mg/kg) or vehicle (PBS) was intraperitoneally injected into mice 1 hour before and after 3-hour ozone (2.5 ppm) or air exposure, and the mice were studied 24 hours later. Preventive and therapeutic treatment with NaHS reduced the ozone-induced increases in the total cells, including neutrophils and macrophages; this treatment also reduced levels of cytokines, including TNF-alpha, chemokine (C-X-C motif) ligand 1, IL-6, and IL-1beta levels in bronchial alveolar lavage fluid; inhibited bronchial hyperresponsiveness; and attenuated ozone-induced increases in total malondialdehyde in bronchoalveolar lavage fluid and decreases in the ratio of reduced glutathione/oxidized glutathione in the lung. Ozone exposure led to decreases in the H2S production rate and in mRNA and protein levels of cystathionine-beta-synthetase and cystathionine-gamma-lyase in the lung. These effects were prevented and reversed by NaHS treatment. Furthermore, NaHS prevented and reversed the phosphorylation of p38 mitogen-activated protein kinase and heat shock protein 27. H2S may have preventive and therapeutic value in the treatment of airway diseases that have an oxidative stress basis.
Keywords: airway inflammation; Animals; Bronchial Hyperreactivity/chemically induced/*drug therapy/metabolism/pathology; bronchial hyperresponsiveness; Bronchoalveolar Lavage; Cystathionine beta-Synthase/metabolism; Cystathionine gamma-Lyase/metabolism; Cytokines/metabolism; Gasotransmitters/*pharmacology; HSP27 Heat-Shock Proteins/metabolism; hydrogen sulfide; Hydrogen Sulfide/*pharmacology; Inflammation/chemically induced/metabolism/pathology; Male; Malondialdehyde/metabolism; mice; Oxidants, Photochemical/*adverse effects/pharmacology; Oxidative Stress; Oxidative Stress/*drug effects; ozone; Ozone/*adverse effects/pharmacology; p38 Mitogen-Activated Protein Kinases/metabolism; RNA, Messenger/metabolism